Bumble bee abundance and richness improves honey bee pollination behaviour in sweet cherry - Eeraerts, Maxime; Smagghe, Guy; Meeus, Ivan (Basic and applied ecology, 2020)
•The pollination behaviour of bumble bees is different than that of honey bees.•Bumble bee richness and abundance improve the pollination behaviour of honey bees.•Bumble’ bees pollination behaviour was not influenced by bee richness or abundance. Pollination service in agricultural crops increases significantly with pollinator diversity and wild pollinator abundance. Differences in the foraging behaviour of pollinating insects are one of the reasons why pollinator diversity and abundance enhances crop pollination. Here, we focused on the foraging behaviour of honey bees and bumble bees in sweet cherry orchards. In addition, we studied the influence of bee diversity and abundance on the foraging behaviour of honey bees and bumble bees. Honey bees were found to visit fewer flowers than bumble bees. Bumble bees also showed a higher probability of changing trees between rows than honey bees. Both visitation rate and probability of row changes of honey bees increased with bumble bee diversity and with bumble bee abundance. We also found that the probability of row changes of honey bees increased with increasing bumble bee abundance. These effects of bumble bee richness and abundance on the pollination behaviour of honey bees can improve the pollination performance of honey bees in crops that depend on cross pollination. Our results highlight the higher pollination performance of bumble bees and the facilitative effect of wild pollinators to crop pollination.